2004
DOI: 10.1002/app.13710
|View full text |Cite
|
Sign up to set email alerts
|

Nylon 6 microfiber obtained by a continuous‐thinning method with a carbon dioxide laser

Abstract: ABSTRACT:We succeeded in producing nylon 6 microfibers with a continuous-thinning method with a carbon dioxide (CO 2 ) laser. A laser-thinning apparatus used to continuously prepare microfibers was developed in our laboratory; it consisted of spools supplying and winding the fibers, a continuous-wave CO 2 -laser emitter, a system supplying the fibers, and a traverse. The laser-thinning apparatus produced microfibers in the range of 100 -2500 m min Ϫ1 . The diameter of the microfibers decreased as the winding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A carbon dioxide (CO 2 ) laser‐thinning method developed by us could easily produce microfibers by irradiating a continuous‐wave CO 2 laser to fibers, such as poly(ethylene terephthalate) (PET),16 nylon 6,17 nylon 66,18 i‐polypropylene,19 poly( L ‐lactic acid) (PLLA),20, 21 and poly(ethylene ‐2,6‐ naphthalate) (PEN)22 fibers without highly skilled techniques. The microfiber obtained by winding on a spool in the winding speed range of 100–2500 m min −1 was monofilament microfiber with a uniform diameter.…”
Section: Introductionmentioning
confidence: 99%
“…A carbon dioxide (CO 2 ) laser‐thinning method developed by us could easily produce microfibers by irradiating a continuous‐wave CO 2 laser to fibers, such as poly(ethylene terephthalate) (PET),16 nylon 6,17 nylon 66,18 i‐polypropylene,19 poly( L ‐lactic acid) (PLLA),20, 21 and poly(ethylene ‐2,6‐ naphthalate) (PEN)22 fibers without highly skilled techniques. The microfiber obtained by winding on a spool in the winding speed range of 100–2500 m min −1 was monofilament microfiber with a uniform diameter.…”
Section: Introductionmentioning
confidence: 99%
“…A laser‐thinning method producing microfiber by irradiating a carbon dioxide (CO 2 ) laser to fibers was developed by us, and an apparatus for the CO 2 laser‐thinning is able to wind the microfiber as a monofilament, at winding speeds ranging from 100 to 2500 m min −1 . The laser‐thinning method has already been applied to a poly(ethylene terephthalate) (PET),5 nylon 6,6 isotactic polypropylene (i‐PP),7 nylon 66,8 and poly( L ‐lactic acid) fibers,9 and the microfibers with diameter range of 1.5–5 μm were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 laser‐thinning method easily yields microfibers without using highly skilled techniques, and it is suitable for producing microfibers of various polymers at a small scale. The CO 2 laser‐thinning method was previously applied to poly(ethylene terephthalate) (PET),5, 6 nylon 6,7 nylon 66,8 isotactic polypropylene,9 and poly( L ‐lactic acid) (PLLA),10 and then their microfibers with a diameter of about 2 μm were obtained. SEM showed that the laser‐thinned (LT) microfibers had smooth surfaces not roughened by laser ablation, which were uniform in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Although the CO 2 laser‐thinning was characterized by the plastic flow accompanied by a molecular orientation and a strain‐induced crystallization, the mechanical properties of the obtained microfiber were insufficient because of the lack of the highly oriented amorphous chains and crystallites 5–10. Therefore, it was necessary to draw and anneal the microfiber obtained to improve its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%